Sex differences in own and other body perception. Issue 2 (15th November 2018) - Burke, Sarah M.; Majid, D. S. Adnan; Manzouri, Amir H.; Moody, Teena; Feusner, Jamie D.; Savic, Ivanka
Abstract: Own body perception, and differentiating and comparing one's body to another person's body, are common cognitive functions that have relevance for self‐identity and social interactions. In several psychiatric conditions, including anorexia nervosa, body dysmorphic disorder, gender dysphoria, and autism spectrum disorder, self and own body perception, as well as aspects of social communication are disturbed. Despite most of these conditions having skewed prevalence sex ratios, little is known about whether the neural basis of own body perception differs between the sexes. We addressed this question by investigating brain activation using functional magnetic resonance imaging during a Body Perception task in 15 male and 15 female healthy participants. Participants viewed their own body, bodies of same‐sex, or opposite‐sex other people, and rated the degree that they appeared like themselves. We found that men and women did not differ in the pattern of brain activation during own body perception compared to a scrambled control image. However, when viewing images of other bodies of same‐sex or opposite‐sex, men showed significantly stronger activations in attention‐related and reward‐related brain regions, whereas women engaged stronger activations in striatal, medial‐prefrontal, and insular cortices, when viewing the own body compared to other images of the opposite sex. It is possible that other body images, particularly of the opposite sex, may be of greater salience for men, whereas images of own bodies may be more salient for women. These observations provide tentative neurobiological correlates to why women may be more vulnerable than men to conditions involving own body perception.